1996
DOI: 10.1002/(sici)1097-0010(199605)71:1<59::aid-jsfa548>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloid Concentration of Potato Tubers Following Exposure to Daylight

Abstract: The total glycoalkaloid concentrations in white‐ (cv Pentland Hawk), pink‐ (cv Kerrs Pink) and red‐ (cv Desiree) skinned potato tubers were measured following 21 days exposure to daylight using high‐performance liquid chromatography. Average daytime irradiance during this period was 232 μmol m−2 s−1. Regardless of cultivar, glycoalkaloid concentrations were increased after light exposure compared with initial concentrations. Glycoalkaloid concentrations fluctuated with time and continuous accumulation of glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…A similar behaviour was observed by Percival, Dixon, and Sword (1996) for the cultivars Kerrs Pink, Pentland Hawk and Desiree. Although an increase of the TGA level was verified after exposure of the tubers to natural light for 21 days, the authors reported that the TGA contents fluctuated during the experiment, with no continuous accumulation of these compounds by the potato varieties studied.…”
Section: Resultsmentioning
confidence: 99%
“…A similar behaviour was observed by Percival, Dixon, and Sword (1996) for the cultivars Kerrs Pink, Pentland Hawk and Desiree. Although an increase of the TGA level was verified after exposure of the tubers to natural light for 21 days, the authors reported that the TGA contents fluctuated during the experiment, with no continuous accumulation of these compounds by the potato varieties studied.…”
Section: Resultsmentioning
confidence: 99%
“…All these factors usually increase the glycoalkaloid concentration in the tubers. In tubers exposed to daylight for 21 days, the content increased 3.6-10 times depending on the cultivar [20]. Mechanical injuries doubled the content [21] and pests caused a 50% increase [22].…”
Section: Introductionmentioning
confidence: 90%
“…After 0, 7, 17, and 36 days, three subsamples were taken, and the content of -solanine was determined as described above. Potato tubers of the cultivar Sava were placed in daylight at room temperature for about 3 weeks to induce the -solanine production [20]. Potato tubers were finely grated by a juicer (Braun MP-80 Juicer), separating the potato juice and the potato pulp.…”
Section: Ageingmentioning
confidence: 99%
“…Such stresses include, principally, light exposure (Dale et al 1993 ;Percival et al 1996) and tuber damage. Tuber damage during harvest and store operations can result in various symptoms including bruising, shatter cracks and splits.…”
Section: Introductionmentioning
confidence: 99%